Revolução Industrial e mudança tecnológica na agricultura européia - Romeiro, Ademar Ribeiro (Revista de História, 1991)
This text approaches questions relative to the transferences in agricultural practices taking place in XVIIl th and XIXth century Europe. Focusing on England, the author examines questions relative to the demographic distribution between the urban and rural areas. The implantation of new instruments and the ack of fertilizers are aspects that are analysed in this text. The transformations coherence draws a parallel to the Industrial Revolution.